Communication Management of the Sidoarjo Deaf Action Community (Aktu) in Resolving Internal Conflict - Hurum Maqshurot Filkhiyam; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2021)
The Sidoarjo Deaf Action Community has a vision to introduce Deaf culture and sign language widely in society. The word